Progress on Rapidly and Self-Assembly Magnetically Responsive Photonic Crystals With High Tunability and Stability - Liu, Nan; Deng, Lugang; Wang, Peixi; Tang, Shuge; Li, Pinle; Wang, Caiqin; Li, Ya; Ayyanu, Ravikumar; Zheng, Fengjiao (Frontiers in Materials, 2022)
Magnetically induced self-assembling is considered as a novel method to form photonic crystals (PCs) by directive arrangement of nanoparticles (NPs) under the magnetic field. The magnetically responsive PCs (MRPCs) become one of the most promising materials due to its adjustable bandgap along with the field intensity and direction, even the rapid and reversible response. In this paper, we review the basic principles of MRPCs, the research progress of magnetically induced self-assembling PCs including: synthesis and modification of magnetically induced NPs, the formation of an ordered structure of MRPCs, the non-spherical materials self-assemble into PC structure and the non-magnetic materials self-assembling into PC structure. And then we also summarize the regulatory factors of the physical and chemical responses under magnetic field; and an outlook of the application of the MRPCs.